2000
DOI: 10.1038/sj.bjp.0702975
|View full text |Cite
|
Sign up to set email alerts
|

CGRP and adrenomedullin binding correlates with transcript levels for Calcitonin Receptor‐Like Receptor (CRLR) and Receptor Activity Modifying Proteins (RAMPs) in rat tissues

Abstract: 1 Putative receptors for CGRP and adrenomedullin have been investigated in the rat. Calcitonin Receptor-Like Receptor (CRLR), in combination with Receptor Activity Modifying Proteins (RAMPs) is hypothesized to bind either CGRP or adrenomedullin. The receptors known as RDC1 and L1 have also been shown to bind CGRP and adrenomedullin respectively. 2 In this study it is shown that rat CRLR cDNA speci®es a CGRP receptor when co-transfected with RAMP-1 cDNA and an adrenomedullin receptor when co-transfected with ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
2
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 38 publications
6
62
2
2
Order By: Relevance
“…CRLR functions as a CGRP 1 receptor when co-expressed with RAMP1 but as an adrenomedullinpreferring receptor in the presence of either RAMP2 or RAMP3 in transfection studies using HEK 293T cells (McLatchie et al, 1998). This basic hypothesis has been supported by further transfection studies from a number of groups (Mu et al, 1998;Kamitani et al, 1999;Chakravarty et al, 2000), however more information is required concerning the relevance of these receptor combinations to the physiological actions of CGRP and adrenomedullin. Whether CGRP 2 receptors are also formed by CRLR and RAMP combinations is not yet known.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…CRLR functions as a CGRP 1 receptor when co-expressed with RAMP1 but as an adrenomedullinpreferring receptor in the presence of either RAMP2 or RAMP3 in transfection studies using HEK 293T cells (McLatchie et al, 1998). This basic hypothesis has been supported by further transfection studies from a number of groups (Mu et al, 1998;Kamitani et al, 1999;Chakravarty et al, 2000), however more information is required concerning the relevance of these receptor combinations to the physiological actions of CGRP and adrenomedullin. Whether CGRP 2 receptors are also formed by CRLR and RAMP combinations is not yet known.…”
Section: Introductionsupporting
confidence: 51%
“…We found a signi®cant correlation between CGRP binding and RAMP1 mRNA expression but the correlation between adrenomedullin binding and RAMP2 expression was not signi®cant (Chakravarty et al, 2000). As an extension to this study we have evaluated the relationship between CGRP and adrenomedullin binding and CRLR/RAMP transcript levels in immortalized cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The simultaneous expression of CLR and RAMP is essential for the expression of functional receptors. Studies on transfection of different cell types have confirmed this hypothesis [63][64][65].…”
supporting
confidence: 55%
“…L'antagoniste CGRP a permis de définir deux types de R-CGRP [3,4]: le R-CGRP 1 sensible aux propriétés antagonistes du CGRP , mais peu sensible aux effets agonistes d'un analogue linéaire, le [Cys(ACM) 2,7] hCGRPα [4] et le R-CGRP 2 , beaucoup moins sensible au CGRP , alors que l'analogue linéaire est agoniste à la concentration de 10 -8 ou 10 -7 M. Les récepteurs de l'ADM (R-ADM) sont, quant à eux, présents dans de nombreux tissus [5]. En dehors de la moelle épinière, la liaison de l'ADM au niveau du système nerveux est faible, contrairement au CGRP [6].…”
Section: Les Récepteurs Du Cgrp Et De L'admunclassified
“…Le foie est un organe pour lequel une expression équivalente des trois RAMP a été observée [17]. Les études de liaison par radioligands ont montré une corrélation entre le phéno-type du récepteur endogène et l'expression tissulaire d'un RAMP donné en présence de CRLR [5]. En d'autres termes, une corrélation élevée existe entre l'expression de RAMP1 et la liaison au CGRP et entre RAMP2 et la liaison à l'ADM.…”
Section: Caractéristiques Généralesunclassified